ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI INSTALASI FARMASI RUMAH SAKIT X KOTA SURAKARTA - Habel Roy Sulo; Elina Hartono; R. A. Oetari (Jurnal Ilmiah Manuntung, 2019)
The development and improvement of pharmacy service has become consumer concern, since this quality of service will affect on consumer satisfaction. The study aimed at assessing the level of outpatient satisfaction at Department of Pharmacy X Hospital In Surakarta City. This study was a survey research, which was conducted using questionnaire by direct interview. A total of 323 respondent were recruited conveniently in the study. The obtained data was then analyzed using Gap analysis to assess the differences in level of quality services between customer perceptions and customer expectations. The study investigates the five dimensions of service quality and identifies the gap between the perception and expectation. The data was analyzed by using SPPS for windows. In general, the result shows that service quality was lower than the expectations of the patients in the studied hospital. The study finding indicated that gap or differences exist on various dimensions between perception and expectation in level quality services. The highest service quality gap was given to Responsiveness followed by Reliability, Empathy, Tangibles and Assurance with the value of - 0,129; - 0,125; - 0,115; - 0,114; and - 0,108 respectively. Patient satisfactions was influenced by health service quality, with the assurance and responsiveness dimensions as the greatest influence on patient satisfaction.